2010
DOI: 10.1007/s10641-010-9612-2
|View full text |Cite
|
Sign up to set email alerts
|

An experiment of fish spillover from a marine reserve in Cuba

Abstract: Several studies on adult fish movement from marine protected areas to zones open to fishing activity conclude spillover is present, but most of these investigations use indirect evidence and small-sized species of little commercial importance. This paper reports the effects of manipulating a density gradient on movements of large-sized and commerciallyimportant fish across "Jardines de la Reina" Marine Reserve boundaries, using tagging methods and visual census. Tagging was carried out using dart tags and modi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 18 publications
1
12
0
Order By: Relevance
“…57,63,134 For example, the redistribution of fishing effort from an MPA can increase the cost of fishing and lower profitability as a result of increased travel distance (and associated costs), increased exploratory fishing, and aggregation of fishing pressure in non-MPA locations. 47,51,135 Observational studies 34,35,86,136 and bioeconomic models 137,138 indicate that stock recovery and ecological spillover (net emigration of adult biomass and larvae) from areas where fishing is prohibited can result in increased fish abundance and catch per unit effort in fishable areas, thereby mitigating some or all of these costs. In addition to changes in fishing costs and catch, shifts in the catchability of target species and redistribution of fishing effort result in market feedbacks (e.g., prices, quantity demanded and supplied); fishers may subsequently adapt by changing their harvest strategies.…”
Section: Mpa Outcomesmentioning
confidence: 99%
See 1 more Smart Citation
“…57,63,134 For example, the redistribution of fishing effort from an MPA can increase the cost of fishing and lower profitability as a result of increased travel distance (and associated costs), increased exploratory fishing, and aggregation of fishing pressure in non-MPA locations. 47,51,135 Observational studies 34,35,86,136 and bioeconomic models 137,138 indicate that stock recovery and ecological spillover (net emigration of adult biomass and larvae) from areas where fishing is prohibited can result in increased fish abundance and catch per unit effort in fishable areas, thereby mitigating some or all of these costs. In addition to changes in fishing costs and catch, shifts in the catchability of target species and redistribution of fishing effort result in market feedbacks (e.g., prices, quantity demanded and supplied); fishers may subsequently adapt by changing their harvest strategies.…”
Section: Mpa Outcomesmentioning
confidence: 99%
“…[26][27][28] Available evidence, although limited, suggests that MPAs that prohibit fishing can lead to enhanced ecological resilience, including resilience to climate fluctuations, 29,30 storm disturbance, 31 and invasive species. 32 Corresponding impacts in areas adjacent to MPAs include increased larval recruitment, 33 spillover of adult fish, 34,35 and reduced fear behaviors among fish. 36 The wide variation in direction and magnitude of MPA ecological impacts has been attributed to MPA governance (e.g., MPA age, size, resource-use rules, and compliance), management capacity (e.g., staff and budget), 24 biophysical factors (e.g., isolation by deep water), and species traits (e.g., range or life history characteristics).…”
Section: Introductionmentioning
confidence: 99%
“…This pattern is also known as spillover effect and has been reported in several longestablished and well-functioning protected areas Alcala et al, 2005;Francini-Filho & Moura, 2008;Halpern et al, 2009). Spillover effects within the JDLR archipelago have been experimentally confirmed through density manipulation of large-size and PeerJ reviewing PDF | (v2013:09:819:2:1:NEW 16 Jan 2014) commercially valuable reef fish species using tagging methods and visual census (Pina-Amargós et al, 2010). Although the study was performed at a relatively small scale, the authors found that net emigration rates of tagged fish were two-fold higher than at control sites when a strong fish density gradient was established after modifying fish abundance (Pina-Amargós et al, 2010).…”
Section: Discussionmentioning
confidence: 67%
“…Spillover effects within the JDLR archipelago have been experimentally confirmed through density manipulation of large-size and PeerJ reviewing PDF | (v2013:09:819:2:1:NEW 16 Jan 2014) commercially valuable reef fish species using tagging methods and visual census (Pina-Amargós et al, 2010). Although the study was performed at a relatively small scale, the authors found that net emigration rates of tagged fish were two-fold higher than at control sites when a strong fish density gradient was established after modifying fish abundance (Pina-Amargós et al, 2010). In addition, anecdotal accounts of spillover effects of adult fish from the JDLR reserve reported by fishers (e.g., "fish leave the reserve and for that reason we catch more fish now than we did before") support the scientific findings.…”
Section: Discussionmentioning
confidence: 95%
“…In coral reef fish, there is some evidence of compensatory immigration from research on recolonization of reefs (Gundermann & Popper 1975; Brock, Lewis & Wass 1979; Syms & Jones 2000; Lowry & Suthers 2004), on territoriality and interspecific competition in damselfishes (Sale 1976; Hixon 1980; Hourigan 1986; Meadows 2001) and on emigration from marine reserves (Amargós et al. 2010).…”
Section: Discussionmentioning
confidence: 99%